(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
The long-term integrity of geoenvironmental containment systems is critical for preventing groundwater contamination, while conventional monitoring is only reactive. This work addresses the need for proactive, predictive monitoring by deriving a novel integral conjugation boundary condition for a smart geobarrier. This condition incorporates real-time sensor data through a Newtonian nudging data assimilation term, providing a mathematically rigorous mechanism to continuously steer a physical model toward observed reality. As an example of application, a boundary value problem for the process of filtrational consolidation is formulated.